Barriers and facilitators in the Strengthening Families Program (SFP 10–14) implementation process in northeast Brazil : a retrospective qualitative study - Abdala, Ingrid Gomes (2020)
This study analyzed contextual barriers and facilitators in the implementation of Strengthening Families Program (SFP 10–14), Brazilian version, a family-based preventive program focused on the prevention of risk behaviors for adolescent health. SFP 10–14 was implemented between 2016 and 2017 for socioeconomically vulnerable families in four Northeast Brazilian states as a tool of the National Drug Policy. A retrospective qualitative study was carried out in which 26 implementation agents participated. Data from 16 individual interviews and two group interviews were analyzed through content analysis. The most recurrent barriers were the group facilitators’ working conditions, weak municipal administration, precarious infrastructure, inadequate group facilitator training methodologies, low adherence of managers and professionals, and funding scarcity. The conditions highlighted as favorable to the implementation were proper intersectoral coordination, engagement of involved actors, awareness of public agency administrators, municipal management efficacy, and efficient family recruitment strategies. Favorable political contexts, engagement of implementation agents, and intersectoral implementation strategies were identified as central to the success of the implementation of SFP 10–14, especially in the adoption of the intervention, community mobilization, and intervention delivery stages. Further studies should combine contexts, mechanisms, and results for a broad understanding of the effectiveness of this intervention in the public sector.